MENGEMBANGKAN KEMAMPUAN PEMECAHAN MASALAH DAN BELIEF CALON GURU MATEMATIKA MELALUI STRATEGI PERKULIAHAN KOLABORATIF - Djamilah Bondan Widjajanti; Wahyudin . (Jurnal Cakrawala Pendidikan, 2015)
Abstract: Developing Mathematics Student-Teachers’ Problem Solving Competence and Belief Through a Collaborative Learning Strategy. This study aimed to analyze the implementation of a collaborative problem-based learning strategy in developing mathematics student-teachers’ problem solving competence and belief in mathematics learning. It was a quasi-experimental study employing a 2 × 2 factorial design with two dependent variables. The subjects were 83 students of Mathematics Education Study Program, Faculty of Mathematics and Natural Sciences, Yogyakarta State University, who took the Discrete Mathematics course in the semester of September - December 2009. The instruments were a test on problem-solving competence, a psychological scale to measure the students' belief, observation sheets, and interview guides. The data were analyzed using two-way MANOVA at a significance level of α = 0.05. The results show that the collaborative problem-based learning strategy is superior to the conventional learning strategy to develop students’ problem solving competence and belief in mathematics learning. Keywords: problem-solving, belief, collaborative